Interaction of Iron Deficiency Anemia and Hemoglobinopathies Among College Students and Pregnant Women: A Multi Center Evaluation in India. (August 2014) - Mohanty, Dipika; Gorakshakar, Ajit C.; Colah, Roshan B.; Patel, Ramesh Z.; Master, Dilip C.; Mahanta, J.; Sharma, Santanu K.; Chaudhari, Utpal; Ghosh, Malay; Das, Sheila; Britt, Reitt P.; Singh, Shawinder; et al.
Abstract Although iron deficiency anemia is very common in India, systematic large studies on the prevalence and hematological consequences of iron deficiency among carriers of β-thalassemia (β-thal) and other hemoglobinopathies are lacking. A multi center project was undertaken to screen college/university students and pregnant women for iron deficiency anemia and various hemoglobinopathies. Fifty-six thousand, seven hundred and seventy-two subjects from six states, Maharashtra, Gujarat, Karnataka, West Bengal, Assam and Punjab, were studied. Iron deficiency anemia was evaluated by measuring zinc protoporphyrin (ZPP) and hemoglobin (Hb) levels, while β-thal and other hemoglobinopathies were detected by measuring the red cell indices and by Hb analysis using high performance liquid chromatography (HPLC). College boys (2.2%), college girls (14.3%) and antenatal women (27.0%) without any hemoglobinopathies had iron deficiency anemia. Among the β-thal carriers, the prevalence of iron deficiency anemia was 17.3% in college boys, 38.1% in college girls and 55.9% in pregnant women, while in the Hb E [β26(B8)Glu→Lys; HBB: c.79G>A] carriers, it was 7.3% in college boys, 25.4% in college girls and 78.0% in antenatal women. In individuals with Hb E disease, the prevalence of iron deficiency anemia varied from 31.2-77.3% in the three groups. A significant reduction in Hb levels was seen when iron deficiency anemia was associated with hemoglobinopathies. However, the Hb A2 levels in β-thal carriers were not greatly reduced in the presence of iron deficiency anemia.